Molecular characterization of sub-frontal recurrent medulloblastomas reveals potential clinical relevance - Chen, Zirong; Yang, Huaitao; Wang, Jiajia; Long, Guoxian; Xi, Qingsong; Chen, Tao; He, Yue; Zhang, Bin; Wan, Feng (Frontiers in Neurology, 2023)
Background Single recurrence in the sub-frontal region after cerebellar medulloblastoma (MB) resection is rare and the underlying molecular characteristics have not been specifically addressed. Methods We summarized two such cases in our center. All five samples were molecularly profiled for their genome and transcriptome signatures. Results The recurrent tumors displayed genomic and transcriptomic divergence. Pathway analysis of recurrent tumors showed functional convergence in metabolism, cancer, neuroactive ligand–receptor interaction, and PI3K-AKT signaling pathways. Notably, the sub-frontal recurrent tumors had a much higher proportion (50–86%) of acquired driver mutations than that reported in other recurrent locations. The acquired putative driver genes in the sub-frontal recurrent tumors functionally enriched for chromatin remodeler-associated genes, such as KDM6B, SPEN, CHD4, and CHD7. Furthermore, the germline mutations of our cases showed a significant functional convergence in focal adhesion, cell adhesion molecules, and ECM–receptor interaction. Evolutionary analysis showed that the recurrence could be derived from a single primary tumor lineage or had an intermediate phylogenetic similarity to the matched primary one. Conclusion Rare single sub-frontal recurrent MBs presented specific mutation signatures that might be related to the under-dose radiation. Particular attention should be paid to optimally covering the sub-frontal cribriform plate during postoperative radiotherapy targeting.